The Great Masquerader: Autoimmune Pancreatitis Presenting as an Obstructive Pancreatic Head Mass and the Avoidance of a Whipple Procedure (Journal of Rangpur Medical College, 2025)
Autoimmune pancreatitis (AIP) is a unique, steroid-responsive focal form of chronic pancreatitis, particularly in the pancreatic head, often presents as a mass-forming lesion with obstructive jaundice, perfectly mimicking pancreatic adenocarcinoma. Distinguishing between these two entities is paramount, as their management is radically different. A 45-year-old male presented with a three-week history of painless jaundice, pruritus, and weight loss. Computed Tomography (CT) revealed a hypodense mass in the pancreatic head measuring 3.5 cm, with abrupt cutoff of the common bile duct and double-duct sign, accompanied by proximal biliary and pancreatic duct dilatation. Serum Carbohydrate Antigen 19-9 (CA 19-9) was elevated at 250 U/mL. The patient was scheduled for a pancreaticoduodenectomy (Whipple procedure). Prior to surgery, a review of the CT by a dedicated pancreatic radiologist noted a subtle "halo sign" around the pancreas. This prompted further testing, which revealed a serum IgG4 level of 650 mg/dL. A FNA cytology via ultrasonogram showed lymphoplasmacytic infiltration and >50 IgG4-positive plasma cells per high-power field, consistent with AIP Type 1. The Whipple procedure was canceled. The patient was started on oral prednisone (40 mg/day). His jaundice resolved within two weeks. A repeat CT scan after 4 weeks of therapy showed a dramatic reduction in the size of the pancreatic head mass and resolution of the biliary dilatation. CA 19-9 normalized. The steroid dose was tapered, and the patient was maintained on azathioprine. He remains asymptomatic at one-year follow-up. This case highlights that AIP must be a mandatory consideration in every patient with a suspected pancreatic head malignancy. The presence of a “halo sign” on imaging and elevated serum IgG4 is crucial diagnostic red flags. A definitive tissue diagnosis is often necessary to prevent unnecessary and morbid surgery. A high index of suspicion and a multidisciplinary approach are essential.J Rang Med Col. 2025 Sep;10(2):166-169